An assessment of driving fitness in patients with visual impairment to understand the elevated risk of motor vehicle accidents. Issue 2 (27th February 2015) - Kunimatsu-Sanuki, Shiho; Iwase, Aiko; Araie, Makoto; Aoki, Yuki; Hara, Takeshi; Nakazawa, Toru; Yamaguchi, Takuhiro; Ono, Hiroshi; Sanuki, Tomoyuki; Itoh, Makoto
Abstract : Objective: To assess the driving fitness of patients with glaucoma by identifying specific areas and degrees of visual field impairment that threaten safe driving. Design: Case–control study. Setting, and participants: This prospective study included 36 patients with advanced glaucoma, defined as Humphrey field analyzer (HFA; 24-2 SITA standard program) measurements of mean deviation in both eyes of worse than −12 dB, and 36 age-matched and driving exposure time-matched normal subjects. All participants underwent testing in a novel driving simulator (DS) system. Participants were recruited between September 2010 and January 2012. Main outcome measures: The number of collisions with simulated hazards and braking response time in 14 DS scenarios was recorded. Monocular HFA 24-2 test results from both eyes were merged to calculate the binocular integrated visual field (IVF). The position of the IVF subfields in which the collision-involved patients had lower sensitivity than the collision-uninvolved patients was compared with the track of the hazard. The cut-off value to predict an elevated risk of collisions was determined, as were its sensitivity and specificity, with the area under the receiver operating characteristic (AUROC) curve. Results: Patients with advanced glaucoma were involved in a significantly higher number of collisions in the DS than the age-matched and driving exposure time-matched normal subjects (119 vs 40, respectively, p<0.0001), especially in four specific DS scenarios. In these four scenarios, IVF sensitivity was significantly lower in the collision-involved patients than in the collision-uninvolved patients in subfields on or near the track of the simulated hazard (p<0.05). The subfields with the largest AUROC curve had values ranging from 0.72 to 0.91 and were located in the paracentral visual field just below the horizontal. Conclusions: Our novel DS system effectively assessed visual impairment, showing that simulators may have future potential in educating patients.